2020
DOI: 10.1111/cen.14394
|View full text |Cite
|
Sign up to set email alerts
|

Prolactinoma in childhood and adolescence—Tumour size at presentation predicts management strategy: Single centre series and a systematic review and meta‐analysis

Abstract: Objective To report the clinical presentation, management and outcomes of young patients with prolactinomas (<20 years) and conduct a systematic review and meta‐analysis. Patients and Design Clinical, biochemical and radiological data (1996‐2018) were collected from our centre. A systematic review and meta‐analysis of published literature (1994‐2019) on prolactinoma (age <20 years) were conducted. Both random and fixed effects meta‐analysis were used to pool outcomes across studies. Results 1 Case series Twent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…19 Moreover, >80% of patients with macroadenomas in our study were 276 female, and this contrasts with the occurrences of sporadic macroprolactinomas in children and adolescents, 277 which are more common in males. 21 Furthermore, ~50% of patients with macroadenomas did not respond 278 to medical therapy and required surgical treatment. This is consistent with a report of pituitary adenomas 279 in MEN1 patients, compared to non-MEN1 pituitary tumors, being less responsive to medical therapy and 280 more aggressive, 22 although another study, which excluded pediatric patients, reported that MEN1-related 281 prolactinomas rarely required surgery.…”
mentioning
confidence: 99%
“…19 Moreover, >80% of patients with macroadenomas in our study were 276 female, and this contrasts with the occurrences of sporadic macroprolactinomas in children and adolescents, 277 which are more common in males. 21 Furthermore, ~50% of patients with macroadenomas did not respond 278 to medical therapy and required surgical treatment. This is consistent with a report of pituitary adenomas 279 in MEN1 patients, compared to non-MEN1 pituitary tumors, being less responsive to medical therapy and 280 more aggressive, 22 although another study, which excluded pediatric patients, reported that MEN1-related 281 prolactinomas rarely required surgery.…”
mentioning
confidence: 99%
“…Prolactinomas are the most frequently encountered pituitary adenoma in clinical practice ( 1 , 20 ). In children, adolescents and young adults, prolactinomas are also the most common pituitary adenoma ( 21 ). Most present as microadenomas in fertile women that are responsive to labelled doses of cabergoline ( 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 38 39 40 ] However, prolactinomas perform differently with medical management in patients lesser than 20 years of age, where macroproactinemia requires multimodal therapy, including surgical intervention. [ 44 ]…”
Section: Discussionmentioning
confidence: 99%
“…In the systematic review and meta-analysis of 22 patients aged less than 20 years with prolactinoma, the authors found that macroprolactinoma (size > 20 mm) is more likely to require multimodality therapy, including surgical intervention. [ 44 ] These patients usually have larger tumors and prolactin levels, and are usually not responsive to cabergoline therapy. However, even giant prolactinomas are shown to be responsive to cabergoline therapy in adults.…”
Section: Alvular H Eart D Iseas...mentioning
confidence: 99%